2005
DOI: 10.1111/j.1462-2920.2005.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial dynamics in spring water of alpine karst aquifers indicates the presence of stable autochthonous microbial endokarst communities

Abstract: Spring water of two alpine karst aquifers differing in hydrogeology but of nearby catchments were investigated for their bacterial population dynamics. Dolomite karst aquifer spring 1 (DKAS 1) represents a dolomitic-limestone karst aquifer spring showing high average water residence time and relative constant flow. Limestone karst aquifer spring 2 (LKAS 2) constitutes a typical limestone karst aquifer spring with a dynamic hydrological regime and discharge. Dolomite karst aquifer spring 1 yielded constantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
125
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 37 publications
15
125
1
3
Order By: Relevance
“…The prokaryotic population densities are similar in the target aquifers of the two aquifer assemblages, ranging from 2.7 × 10 6 to 3.8 × 10 8 cells L −1 over time (Opitz et al, 2014), which is similar to microbial abundances observed in spring water of alpine karst aquifers (Farnleitner et al, 2005). Quantitative PCR targeting bacterial and archaeal 16S rRNA genes suggested that archaea form a fraction of 0.03-8.2% of the total microbial population across different transect locations.…”
Section: Microbial Communitiessupporting
confidence: 52%
See 2 more Smart Citations
“…The prokaryotic population densities are similar in the target aquifers of the two aquifer assemblages, ranging from 2.7 × 10 6 to 3.8 × 10 8 cells L −1 over time (Opitz et al, 2014), which is similar to microbial abundances observed in spring water of alpine karst aquifers (Farnleitner et al, 2005). Quantitative PCR targeting bacterial and archaeal 16S rRNA genes suggested that archaea form a fraction of 0.03-8.2% of the total microbial population across different transect locations.…”
Section: Microbial Communitiessupporting
confidence: 52%
“…Carbonate rocks cover over 20% of the Earth's ice-free continental area and karst aquifers represent important drinking water reservoirs, supplying up to 25% of the world's population with fresh water (Ford and Williams, 2015). Previous investigations of the microbial inventory of karst aquifers primarily focused on spring water or caves that allow easier access, pointing to the presence of autochthonous microbial endokarst communities but also to high temporal dynamics, indicated by the episodic occurrence of allochthonous soil bacteria within the spring water communities (Farnleitner et al, 2005;Pronk et al, 2008;Shabarova et al, 2013). However, less information is available for groundwater obtained from drilled boreholes within a karstic limestone setting (Gray and Engel, 2013).…”
Section: The Aquadiva Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique makes it possible to compare the microbial biocenoses from different samples, and to analyse their similarities using statistical methods. Non-parametric statistical analyses can be applied to combine these results with other sets of environmental data (Dewettinck et al 2001;Farnleitner et al 2005;Fromin et al 2002). Microscopic analyses and flow cytometry, combined with specific coloration techniques, can be used to characterise the morphological diversity of microbial communities, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…In groundwater from different types of aquifers, planktonic cell numbers often range between 10 4 and 10 6 cells mL −1 , about two orders of magnitude lower than the number of benthic cells. The culturable counts are much lower, often less than 10 cells mL −1 (Farnleitner et al 2005;Haveman and Pedersen 2002;Marxsen 1988;Ultee et al 2004). These studies show that the number of attached (benthic) cells most often exceeds the number of suspended (planktonic) cells, and that most of the bacteria are non culturable and in a state of reduced activity.…”
Section: Bacterial Abundance and Activity In Aquifersmentioning
confidence: 99%